EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) DAN THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) DENGAN PENDEKATAN SAINTIFIK PADA MATERI OPERASI ALJABAR DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA KELAS VIII SMP NEGERI DI SURAKARTA - Hidayat, Edisut Taufik; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objectives of research were to find out: 1) which one is better learning achievement, scientific NHT, scientific TAPPS, or scientific classical, 2) which one is better learning achievement, students with high, medium, or low AQ, 3) in each learning models, which one is better learning achievement, students with high, medium, or low AQ, 4) in each AQ level, which one is better learning achievement, scientific NHT, scientific TAPPS, or scientific classical. This research was the quasi experimental research with 3Ã3 factorial design. The population of research was all grade VIII students of Junior High School in Surakarta. The samples were chosen by using stratified cluster random sampling. The instruments that used were achievement test and Adversity Quotient (AQ) questionare. The proposed hypothesis of the research were tested by using the unbalanced two-way ANOVA. The results of this research were as follows. 1) Scientific NHT had better learning achievement than scientific TAPPS and scientific classical, while scientific TAPPS had better learning achievement than scientific classical. 2) The students with high AQ had better learning achievement than medium and low AQ, while the students with medium AQ had better learning achievement than low AQ. 3) In scientific NHT, the students with high, medium, and low AQ had the same learning achievement. In scientific TAPPS, the students with high AQ had better learning achievement than medium AQ, while the students with high and medium AQ had better learning achievement than low AQ. In scientific classical, the students with high AQ had better learning achievement than medium and low AQ, while the students with medium AQ had better learning achievement than low AQ. 4) At the students with high AQ, scientific NHT and scientific classical had the same learning achievement with scientific TAPPS, while scientific NHT had better learning achievement than scientific classical. At the students with medium AQ, scientific NHT had the same learning achievement with scientific TAPPS, while scientific NHT and scientific TAPPS had better learning achievement than scientific classical. At the student with low AQ, scientific NHT had better learning achievement than scientific TAPPS and scientific classical, while scientific TAPPS had the same learning achievement with scientific classical.Keywords: scientific NHT, scientific TAPPS, scientific classical, Adversity Quotient (AQ), Achievement